Easing Program Comprehension by Sharing Navigation Data - DeLIne, Robert; Czerwinski, Mary; Robertson, George (Proceedings of the IEEE Symposium on Visual Languages and Human-Centered Computing, 2005)
Large software projects often require a programmer to make changes to unfamiliar source code. This paper describes a set of tools, called Team Tracks, designed to ease program comprehension by showing the source code navigation patterns of fellow development team members. One technique shows a list of Related Items, given that the user is viewing a given method or class. Another technique shows the Favorite Classes, by showing a class hierarchy view that hides less frequently visited classes, methods, and members. Two user studies, a laboratory study and a field study, were run to evaluate the effectiveness of these techniques. The results of the two studies demonstrate that sharing navigation data can improve program comprehension and are subjectively preferred by users.
[best paper awared]